Penerapan Manajemen Pendidikan yang Mendukung Karakter Peserta Didik pada SMPK STA. Theresia Kupang - Yohana Elu; Henny A Manafe (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Education is a conscious effort that is carried out regularly and systematically to obtain positive changes. The output of education must be able to provide changes in at least 4 important aspects, namely: (1) knowledge, (2) skills, (3) attitudes (affective), and (4) various characters needed in life (attitudes). This research uses qualitative research methods because the problems studied are holistic, complex, dynamic, and full of meaning, so data on social situations is impossible with quantitative research. Research data will be obtained from the Head of School, Deputy Head of Curriculum, Deputy Head of Student Affairs, Deputy Head of Infrastructure, Deputy Head of Public Relations, Catholic Religious Education Teacher, Citizenship Education Teacher, Counseling Guidance Teacher, homeroom teacher, and several teachers and several students of SMPK Sta. Theresia Kupang. Even though SMPK Sta. Theresia Kupang has implemented education management that supports student character but there are still students who violate school rules so they are categorized as students with bad morals. Why this is still happening and how to overcome it will be the focus of this research study to contribute to SMPK Sta Theresia Kupang and various parties in need.